OHP-001 A Survey of Physicians' Opinions on Bioequivalent Pharmaceutical Products. (12th March 2013) - Ratnaparkhi, M; Ghodke, R; Patil, M
Abstract : Background: Bioequivalence studies are basically comparative bioavailability studies designed to establish equivalence between generic and innovator products. Pharmaceutical equivalence is the pre-condition of bioequivalence. Medicinal products are described as pharmaceutically equivalent if they contain the same amount of the same active substances in the same dosage forms that meet the same or comparable standards. Purpose: To discover the opinions of physicians on bioequivalent pharmaceutical products and their use. Materials and Methods: 130 physicians were given a form with 10 questions. In this survey, questionnaires were answered by face to face interview. Results: Conclusions: The questionnaire shows that physicians are uncertain about whether generic drugs are as effective as their originals. Furthermore the results revealed that physicians prefer not to use generic drugs for themselves or their relatives. Most of them opined that generics are safe but less effective and therefore they avoid prescribing generic drugs especially antibiotics. No conflict of interest.